Challenges and Opportunities of Artisanal Female Entrepreneurship in Guayaquil, Ecuador and Its Sustainable Impact - Figueroa Guijarro, Mary; Ramos Suárez, Luisa; Palma Martínez, Andrés; Plaza Vargas, Angel Marcel (EASI: Engineering and Applied Sciences in Industry, 2026)
This study aimed to identify the main challenges and opportunities of women’s artisanal entrepreneurship in Guayaquil and to analyze its relationship with economic, social, and environmental sustainability. The research involved 93 artisans from the Guayaquil Handicraft Market, using a questionnaire validated with adequate levels of reliability (α = 0.82–0.88; KR-20 = 0.76–0.81) and statistical consistency (CFI = 0.92; TLI = 0.90; RMSEA = 0.07). The results show that, in the economic dimension, the educational level of artisans is associated with the legal formalization of businesses (χ² = 19.3; p = 0.05; V = 0.32), and social security affiliation is related to the perception of income improvement (χ² = 12.6; p = 0.048; V = 0.28), reaching an average score of 70/100. In the social dimension, participation in associations strengthened family and community roles (χ² = 8.2; p = 0.041), with an average score of 75. In the environmental dimension, the greatest weakness was observed: 87.1% of artisans do not recycle and 91.4% dispose of waste with regular garbage, resulting in an average score of only 35. The overall sustainability index was 65/100. In conclusion, although these entrepreneurs constitute a cultural and economic driver for the city, public policies and training programs are needed to strengthen integral sustainability, with particular emphasis on the environmental dimension.
Keywords: Female entrepreneurship; Artisanal sector; Sustainability; Challenges and opportunities